2015
DOI: 10.1155/2015/602360
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of the Flavonoid Chrysin against Methylmercury-Induced Genotoxicity and Alterations of Antioxidant Status,In Vivo

Abstract: The use of phytochemicals has been widely used as inexpensive approach for prevention of diseases related to oxidative damage due to its antioxidant properties. One of dietary flavonoids is chrysin (CR), found mainly in passion fruit, honey, and propolis. Methylmercury (MeHg) is a toxic metal whose main toxic mechanism is oxidative damage. Thus, the study aimed to evaluate the antioxidant effects of CR against oxidative damage induced by MeHg in Wistar rats. Animals were treated with MeHg (30 µg/kg/bw) in pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 66 publications
1
18
0
1
Order By: Relevance
“…Knowledge about blood micronutrient levels is of great importance in Brazilian Amazon, since many publications have shown that several nutrients modify the toxicokinetics and toxicodynamics of Hg 2,9,10,26,27 , which is particularly interesting in the context of this current investigation since numerous studies have reported high Hg levels in hair, blood and plasma among Amazonian populations [5][6][7] . Our findings of seasonal blood variation of essential metals (Cu, Se and Zn), carotenoids and vitamin E are probably a result of seasonal variations in food availability.…”
Section: ▄ Discussionmentioning
confidence: 95%
“…Knowledge about blood micronutrient levels is of great importance in Brazilian Amazon, since many publications have shown that several nutrients modify the toxicokinetics and toxicodynamics of Hg 2,9,10,26,27 , which is particularly interesting in the context of this current investigation since numerous studies have reported high Hg levels in hair, blood and plasma among Amazonian populations [5][6][7] . Our findings of seasonal blood variation of essential metals (Cu, Se and Zn), carotenoids and vitamin E are probably a result of seasonal variations in food availability.…”
Section: ▄ Discussionmentioning
confidence: 95%
“…ROS induces the expression of NF-κB, a key transcription factor in the inflammatory response, as well as a variety of proteins linked with oxidative stress-associated reactions. In addition, phytochemicals with antioxidant activity, such as carotenoid (Caramujo et al, 2012) and polyphenols including phenolic acids (Sevgi et al, 2015), flavonoids (Manzolli et al, 2015) and stilbenes (Biais et al, 2017), have been extensively used to reduce toxicity triggered by toxic chemicals. lymphocytes of rats treated with 1, 3, 5 and 10 μg ml of CMIT.…”
Section: Image Analysismentioning
confidence: 99%
“…Analyzing the phytochemical profile of S. brasiliensis, Almeida et al (2010) noticed the presence of tannins, quinones, and triterpens, while Santos et al (2014) showed that the ethyl acetate fraction from the bark of S. brasiliensis contains aurones, catechins, chalcones, and saponins (Santos et al, 2014). On one hand, studies demonstrated that some of those compounds have protective and antigenotoxic effect (Rodríguez-García, 2013;Manzolli et al, 2015). On the other hand, compounds such as saponins were noticed to have genotoxic effect on human lymphocytes (Kalachaveedu et al, 2014).…”
Section: Schinopsis Brasiliensismentioning
confidence: 99%